An overview of the biological ammonia treatment, model prediction, and control strategies in water and wastewater treatment plant / Fuzieah Subari ... [et al.] - Subari, Fuzieah; Harisson, Hafni Fatini; Kasmuri, Nor Hazelah; Abdullah, Zalizawati; Hanipah, Suhaiza Hanim (Universiti Teknologi MARA, 2022)
Water disruption has always been a major issue in Malaysia. The reason for the frequent water disruption is due to the shutdown of water treatment plant (WTP) for unable to process contaminated raw water from the river. In wastewater treatment plant (WWTP), main source of ammonia is from the breakdown of proteins and amino acids in organic waste. Typically, ammonia is not fully removed from the WWTP and most of the ammonia is being discharged together with the plant effluent into the river streams. High levels of ammonia in the water exerts an oxygen demand which causes oxygen depletion. Hence, affecting the aquatic ecosystem and creates a toxic environment for the aquatic life. Biological treatment is known to be the most cost saving method as it only constructs of simple components, chemical free treatment and producing no harm by-products which later cause cost increment for additional treatment. Furthermore, biological treatment is capable in producing high quality treated drinking water that meets the standard water guidelines and regulations. In this paper, the aim is to conduct an overview on the application of biological treatment as an alternative treatment method of ammonia removal in water and wastewater treatment plant. This overview presents the cohesive approach of biological treatment in water and wastewater treatment plant, source of ammonia pollution, standard implies on ammonia concentration to control potential hazards, reported cases and recent pollution status of ammonia globally. In addition, the use of an artificial intelligence for model prediction and control strategies for water treatment have been included in this overview.